(untitled) (Research, Society and Development, 2020)
Objective: To analyze the health of the male population in prison situation at the national level and in the state of Tocantins. Method: Systematic review carried out in the VHL and Google Scholar database for the keywords "health" and "prison system" between the years 2015 to June 2020, including articles published in Portuguese. For quantitative analysis by frequency, the publication data, place where the study was carried out, objective, central object of the research, research method and results were analyzed. Results: Limitations in health care for this population were evidenced in both spheres analyzed, such as the lack of health care in one of the units, the constant lack of health professionals, the absence of emergency services, overcrowding, among others. As a result of the precarious investment in health for this population, a high incidence of mental, infectious and contagious diseases and oral diseases was observed, in addition to the acute complications resulting from violence. Conclusion: The need for investment-based change is highlighted so that, in addition to effective and efficient access to health, prison units are less unhealthy environments.